2004
DOI: 10.3201/eid1006.030662
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Home Residents andEnterobacteriaceaeResistant to Third-Generation Cephalosporins

Abstract: Limited data identify the risk factors for infection with Enterobacteriaceae resistant to third-generation cephalosporins among residents of long-term-care facilities. Using a nested case-control study design, nursing home residents with clinical isolates of Enterobacteriaceae resistant to third-generation cephalosporins were compared to residents with isolates of Enterobacteriaceae susceptible to third-generation cephalosporins. Data were collected on antimicrobial drug exposure 10 weeks before detection of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…Previous antibiotic exposure, in particular to fluoroquinolones and third generation cephalosporins, is frequently described to be associated with carriage of ESBL-producing bacteria in nursing home residents (Mendelson et al, 2005;Sandoval et al, 2004). This appears to be a dose related process since it was shown that the duration of exposure plays an important role in the selection of resistant strains (Rooney et al, 2009;Tinelli et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Previous antibiotic exposure, in particular to fluoroquinolones and third generation cephalosporins, is frequently described to be associated with carriage of ESBL-producing bacteria in nursing home residents (Mendelson et al, 2005;Sandoval et al, 2004). This appears to be a dose related process since it was shown that the duration of exposure plays an important role in the selection of resistant strains (Rooney et al, 2009;Tinelli et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…LTCFs are faced with methicillin-resistant Staphylococcus aureus, MRSA. Currently, colonization by MRSA has reached staggering proportions in LTCFs [13][14][15][16][17][18]. Furthermore, multidrug resistant (MDR) Gram-negative pathogens (especially Escherichia coli, Klebsiella pneumoniae and Acinetobacter baumannii harboring extended-spectrum beta-lactamases/cephalosporinases that confer resistance to cefotaxime, ceftazidime, ceftriaxone and carbapenemases (e.g.…”
Section: An Overview Of Infections In the Elderly And Ltcfsmentioning
confidence: 99%
“…Both ciprofloxacin and trimethoprim-sufamethoxazole use was linked to dissemination of ESBL producing organisms in this report, unlike the earlier outbreak in Massachusetts in which ceftazidime use was the driving force for selection and proliferation [32]. Other publications have since followed documenting the presence of such enzymes in LTCFs [37][38][39][40]. Evolution and progression to carbapenem resistance in Enterobacteraceae soon followed as a result of carbapenem therapy widely accepted for treatment of patients with ESBL harboring bacteria [14].…”
Section: Epidemiologymentioning
confidence: 54%